2014
DOI: 10.4110/in.2014.14.1.14
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Activation in T Helper 17 Cell Differentiation

Abstract: CD28/T cell receptor ligation activates the NF-κB signaling cascade during CD4 T cell activation. NF-κB activation is required for cytokine gene expression and activated T cell survival and proliferation. Recently, many reports showed that NF-κB activation is also involved in T helper (Th) cell differentiation including Th17 cell differentiation. In this review, we discuss the current literature on NF-κB activation pathway and its effect on Th17 cell differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…Immune suppression by TGF-β is achieved by regulating cells in adaptive immunity components, such as T and B cells, as well as in innate immunity components, such as natural killer (NK) cells [ 42 , 53 , 54 ]. Additionally, it was recently reported that TGF-β suppresses immune responses by promoting regulatory T cell (Treg) induction and Th17 differentiation from conventional T cells [ 43 , 44 ]. Because forkhead box protein 3 (Foxp3) is expressed when T cells become Treg, we examined whether Foxp3 is increased in T cells after stimulation of CD40L with anti-CD40L agonistic Ab or by co-culture with CD40-expressing MDA-MB231 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune suppression by TGF-β is achieved by regulating cells in adaptive immunity components, such as T and B cells, as well as in innate immunity components, such as natural killer (NK) cells [ 42 , 53 , 54 ]. Additionally, it was recently reported that TGF-β suppresses immune responses by promoting regulatory T cell (Treg) induction and Th17 differentiation from conventional T cells [ 43 , 44 ]. Because forkhead box protein 3 (Foxp3) is expressed when T cells become Treg, we examined whether Foxp3 is increased in T cells after stimulation of CD40L with anti-CD40L agonistic Ab or by co-culture with CD40-expressing MDA-MB231 cells.…”
Section: Discussionmentioning
confidence: 99%
“…IL-17-mediated proliferation of MDA-MB231 cells was inhibited by the treatment with a STAT3 inhibitor AG490 and anti-IL-17 neutralizing antibody ( Fig 5 ). CD40L is expressed in many cells including mast cells, macrophages, basophils, NK cells, B cells, smooth muscle cells, endothelial cells, and epithelial cells [ 44 ]. Based on the activated T cells, it seems that these cells also get a signal through CD40L found on the surface of the cells by interacting with CD40 on the surface of the MDA-MB231 cells.…”
Section: Discussionmentioning
confidence: 99%
“…It also inhibits production of IFNγ by Th1 cells [ 42 ]. Another study supports the importance of NF-κB activation in Th17 cell differentiation [ 44 ]. Therefore, one possibility could be that CS inhibits cytokine expression by the inhibition of NF-κB activation.…”
Section: Discussionmentioning
confidence: 52%
“…IFN-γ-producing Th1 cells and IL-17-producing Th17 cells are known to cause joint destruction by promoting synovial inflammation and osteoclast formation ( Annunziato et al, 2009 ). Th1 and Th17 cells induce arthritis by regulating immune responses in mice and humans ( Damsker et al, 2010 ; Park et al, 2014 ). Mice with CIA exhibit increased levels of IFN-γ and IL-17 expressed by Th1 and Th17 cells in the lymph nodes ( Xuzhu et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%